A comparison of experimental and computational heat transfer results for a leading edge impingement system - Pearce, R; Ireland, P; Dane, E; Telisinghe, J (MDPI, 2018)
Leading edge impingement systems are increasingly being used for high pressure turbine blades in gas turbine engines, in regions where very high heat loads are encountered. The flow structure in such systems can be very complex and high resolution experimental data is required for engine-realistic systems to enable code validation and optimal design. This paper presents spatially resolved heat transfer distributions for an engine-realistic impingement system for multiple different hole geometries, with jet Reynolds numbers in the range of 13,000–22,000. Following this, Reynolds-averaged Navier-Stokes computational fluid dynamics simulations are compared to the experimental data. The experimental results show variation in heat transfer distributions for different geometries, however average levels are primarily dependent on jet Reynolds number. The computational simulations match the shape of the distributions well however with a consistent over-prediction of around 10% in heat transfer levels.